EFL STUDENTS’ READING HABIT THROUGH EXTENSIVE READING IN HIGHER EDUCATION - Anisa Rahma, Endah; Elvia Jakfar, Ana; Rahmatillah, Refanja; Irna Liyana, Cut; Hasni, Jusnaini (English Review: Journal of English Education, 2025)
This study aims to investigate Indonesian college students’ reading habits. 60 non-English major students who took Extensive Reading course involved in this study in the sixth semester. Previous research has discussed related to English major students’ reading habit, however this study focuses on non-English major students’ reading habit. Descriptive quantitative research was used to reveal the students’ reading habit in English. Data were collected from questionnaire about reading habit activity adapted from Mikulecky and Jeffries (1996). The results indicated that all of students agreed that reading aloud helps them to improve their reading (95%). 96% of them also agree that reading English slowly makes more understand. Besides, most of them (95%) agreed that learning grammar help them to understand more in reading English and 98% of them also agreed that learning vocabulary supported them to understand more English. Majority of them (95%) need to know every word in order to understand English material. 95% of them also agreed that pronouncing every word helps them to read well in English. It can be concluded that Reading slowly and learning vocabulary support them to understand more in reading. This finding confirms that the language teachers or lecturers should be able to help their students cope with foreign language reading anxiety by creating a learning environment which is less stressful. This study provides pedagogical implication that provides significant pedagogical implication for language practitioners and students in creating enjoyable atmosphere in reading class and provide the reading material based on students need.